Diagnosis and Treatment of Acute Intermittent Porphyria - Bai, Jie; Wang, Zhi Hong (Zhōngguó yīxué kēxuéyuàn xuébào, 2017)
Acute intermittent porphyria (AIP) is a metabolic disease caused by hepatic deficiency of hydroxymethylbilane synthase. Its clinical manifestations include acute abdominal pain,neuropsychological abnormalities,and red urine. Due to its low incidence and varied clinical symptoms,the rates of misdiagnosis and mistreatment were particularly high. Biochemical testing and gene detection contribute to diagnosis. Management strategies include intravenous administration of human haemin,carbohydrate loading and symptomatic treatment.